Characteristics of laboratory indicators when prescribing nitrates and amlodipine to patients with chronic heart failure of ischemic and hypertensive genesis - N. A. Matsegora; N. Yu. Ilikchiieva (Kazimierz Wielki University, 2017)
On the background of hemodynamic overload of the heart, coronary insufficiency and arterial hypertension, the hypoxic phenomena are formed, which modify metabolic processes in the direction of activation of endogenous intoxication, which are reflected in hematological and biochemical indices. Therefore, the laboratory data reflecting these violations are essential and useful for assessing the patient's condition. However, in many literary sources there are mostly the peculiarities of clinical and functional parameters that are characteristic of CHF, and, at all, there are no definite comparative characteristic of complex clinical and laboratory studies based on the stages (HF 2A and HF 2B) and their dependence on the prescribed treatment, at that time as the analysis of survival in CHF patients in subgroups, conducted in the framework of multicenter studies SAVE, SOLVD, TRACE, etc., clearly indicates the adverse effects of nitrates on the course and prognosis of CHF Objective. To conduct a comparative analysis of laboratory parameters in course of treatment of patients with ischemic heart disease and hypertension complicated by HF 2A and 2B with the use various vasodilators (nitrates and amlodipine) which are prescribed on the background of standard therapy of CHF. Results of the research. The research was conducted in the cardiology department of theMilitaryMedicalClinicalCenter of the Southern Region. We examined 84 patients with ischemic heart disease in combination with hypertension, complicated HF 2A: 18 patients were prescribed nitrates and 18 - amlodipine; and 2B: 22 patients were prescribed nitrates and 24 - amlodipine on a background of standard complex therapy of CHF of a corresponding degree. The average age was 72.29 ± 1.66 years, by gender, men dominated (86.7%). According to hematological and biochemical studies before treatment, more definite changes of inflammatory and intoxication character in patients with ischemic heart disease and hypertension are in groups with HF 2B than HF 2A, which is associated with a more significant endogenous intoxication of the body caused by hemodynamic overload of small and large blood circulation circles. The prescription of amlodipine, according to most of the studied parameters, was more physiologically than with nitrates, despite their high vasodilating ability. The obtained dynamics of biochemical indicators showed a moderately expressed negative effect of nitrates on the functional state of the liver and kidneys, which makes it advisable to narrow the indications for their appointment to patients with CHF.